Сильный глобальный аттрактор трехмерной системы уравнений навье–стокса в неограниченной каналоподобной области - Горбань, Н.В.; Капустян, А.В.; Капустян, Е.А.; Хоменко, О.В. (Проблемы управления и информатики, 2015)
Розглянуто модифіковану тривимірну систему Нав’є–Стокса в необмеженій області, що задовольняє нерівності Пуанкаре. Доведено однозначну глобальну розв’язність, для відповідної напівгрупи встановлено існування глобального атрактора в сильній топології фазового простору, показано збіжність одержаних атракторів до множини повних обмежених траєкторій 3D-системи Нав’є–Стокса. The modified three-dimensional Navier–Stokes system in unbounded domain satisfying the Poincare inequality is considered. The unique global solvability is proved, the existence of a global attractor for the corresponding semigroup in the strong topology of the phase space, is obtained the convergence of these attractors to the set of complete bounded trajectories of 3D-Navier–Stokes system is shown.